GREEN BUDGETING : STRATEGI PERENCANAAN KEUANGAN BERBASIS SUSTAINABILITY : STUDI SLR - Cici Nurdianti; Anggela Desisca; Intan Putri Suryati (Yayasan Nuraini Ibrahim Mandiri, 2025)
This article discusses the determine green budgeting with sustainabiliity based financial planning strategies. Indonesia is prone to natural disasters because it is located in a danger zone. To maintain its sustainability, government policies must consider the condition of the surrounding environment. In Law No. 32/2009 on Environmental Protection and Management, the central government and local governments are obliged to provide an adequate budget for environmental sustainability. This research uses the Systematic Literature Review (SLR) method with approach PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The research data population consists of more than 20 journals from 2021-2025 which focus on Green Budgeting, Financial Planning and Sustainability. The results of this study show that Green Budgeting and sustainability-based financial planning strategies prove to be crucial in the management control system. It is very important as an innovative method that integrates environmental sustainability values into budget management.